2005
DOI: 10.1128/aem.71.1.247-254.2005
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Escherichia coli O157:H7 on Stainless Steel: Effect of Exopolysaccharide and Curli Production on Its Resistance to Chlorine

Abstract: The resistance of Escherichia coli O157:H7 strains ATCC 43895-, 43895-EPS (an exopolysaccharide [EPS]-overproducing mutant), and ATCC 43895؉ (a curli-producing mutant) to chlorine, a sanitizer commonly used in the food industry, was studied. Planktonic cells of strains 43895-EPS and/or ATCC 43895؉ grown under conditions supporting EPS and curli production, respectively, showed the highest resistance to chlorine, indicating that EPS and curli afford protection. Planktonic cells (ca. 9 log 10 CFU/ml) of all stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
199
2
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(212 citation statements)
references
References 46 publications
(56 reference statements)
5
199
2
6
Order By: Relevance
“…We previously reported that E. coli O157:H7 is not an invasive organism and that a mutation in the csgD gene does not increase the invasion ability of the mutant compared to the E. coli O157:H7 wild-type strain (43). Although it has been reported that curli production by E. coli O157:H7 enhances biofilm formation on inert surfaces, i.e., stainless steel (37,38), our data do not support these findings. In our hands, the csgD gene product of E. coli O157:H7 may be controlling the expression of an adhesive factor required for hyperadherence to tissue culture cells and/or a factor necessary for biofilm formation because the csgD mutant strain was unable to form biofilms on PVC plastic plates.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We previously reported that E. coli O157:H7 is not an invasive organism and that a mutation in the csgD gene does not increase the invasion ability of the mutant compared to the E. coli O157:H7 wild-type strain (43). Although it has been reported that curli production by E. coli O157:H7 enhances biofilm formation on inert surfaces, i.e., stainless steel (37,38), our data do not support these findings. In our hands, the csgD gene product of E. coli O157:H7 may be controlling the expression of an adhesive factor required for hyperadherence to tissue culture cells and/or a factor necessary for biofilm formation because the csgD mutant strain was unable to form biofilms on PVC plastic plates.…”
Section: Discussioncontrasting
confidence: 57%
“…Attachment and biofilm formation by E. coli O157:H7 on food products and containers are a public health concern, and since E. coli O157:H7 has been shown to form biofilms on inert surfaces (37,38,45), our current study was intended to target adhesion to these surfaces. Thus, mutations in specific E. coli O157:H7 adhesins and/or mediators of adherence were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the function of amyloid fibrils is assumed to be related to enhanced adhesion to surfaces (49) and biofilm formation, but they may also increase resistance to chlorine (55) and resistance to chemical and enzymatic digestion (45). The function in activated sludge flocs is still unknown but may be related to the aggregation of microorganisms internally in microcolonies, whereas it is more uncertain what the function is in the filamentous bacteria, which were also shown to produce amyloids (32).…”
mentioning
confidence: 99%
“…It has been previously shown that biofilm-producing E. coli strains are more resistant to chlorine (De Beer et al, 1994;Ryu and Beuchat, 2005) and that biofilm formation is important for protecting bacteria in harsh non-host environments (Stewart et al, 2013). Ryu and Beuchat (2005) demonstrated that the viability of an E. coli O157 strain was completely unaffected by chlorine doses as high as 10 mg/l chlorine for 10 min at 12°C, compared to control strains in which an 8 log 10 inactivation was observed. Remarkably, when this same strain was allowed to form biofilms on a solid support (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Flagella promote bacterial motility, which, in turn, is positively associated with biofilm formation (Wood et al, 2006). Biofilm formation is an important strategy used by bacteria to survive unfavourable environmental conditions, and the formation of biofilms has been shown to promote resistance to chlorine, UV radiation (UVC), oxidative damage and even predation (Bianco et al, 2006;Elasri and Miller, 1999;Ryu and Beuchat, 2005;Vogeleer et al, 2014) -important microbial reduction strategies used during waste water treatment. Consequently, the uspC-IS30-flhDC polymorphism may play an important adaptive strategy in these naturalised bacterial populations towards colonisation and survival in tertiary treated waste water.…”
Section: Introductionmentioning
confidence: 99%